Upaya Meningkatkan Hasil Belajar IPS Melalui Model Pembelajaran Think Pair Share dengan Media Audio Visual pada Peserta Didik Kelas V SDN 3 Langkai Palangkaraya - Rini Utari; Ichyatul Afrom (Bitnet: Jurnal Pendidikan Teknologi Informasi, 2018)
This study aims to improve learning outcomes and find out how the activities of students during the learning process using the Think Pair Share model with Audio Visual media. The type of this research is class action research (PTK) with research subjects all of the fifth-grade students of the Langkai Palangkaraya SDN-3 totaling 30 students. Data collection of this study uses observation and tests and data analysis using qualitative and quantitative data analysis. The results of the study: (1) The activity of students is good which is shown by the acquisition of the results of observations, namely in the first cycle the number of scores 46 with an average value of 3.06. (2) The learning outcomes of students are increased as indicated by the acquisition of an average value of 74.3 in cycle I. The completeness of learning in a classical manner also increases with a value of 100%.